2002
DOI: 10.1016/s0736-0266(01)00082-1
|View full text |Cite
|
Sign up to set email alerts
|

Tissue response during monofocal and bifocal leg lengthening in patients

Abstract: The purpose of this investigation was to compare the tissue response during mono-and bifocal limb lengthening. The study includes four patients undergoing leg lengthening. All patients started out bifocally with a total diurnal distraction of 1.75 mm, but proceeded monofocally with a rate of 1 mm a day when the distal distraction was terminated due to contractures or pain. The tissue response was monitored by registration of axial force in the distraction rods. The force increased linearly during bifocal lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…A A 16 m Tumor US re 220 normal B A 61 m Trauma US re 72 verzögert B A 24 m Trauma OS li 95 normal E M 12 m Tumor US re 115 kritisch F F 35 m Tumor US li 83 überbrückt 7 G S 20 w Trauma US li 51 normal 3 H M 15 m Trauma US li 93 kritisch 5 J T 32 m Trauma US li 110 überkritisch K R 33 m Trauma US li 62 [1]. Aus diesen Betrachtungen folgt, daß beide Komponenten gemeinsam eher einen konstanten als einen progressiven Einfluß auf die Gesamtkraft haben.…”
Section: Materials Und Methodeunclassified
“…A A 16 m Tumor US re 220 normal B A 61 m Trauma US re 72 verzögert B A 24 m Trauma OS li 95 normal E M 12 m Tumor US re 115 kritisch F F 35 m Tumor US li 83 überbrückt 7 G S 20 w Trauma US li 51 normal 3 H M 15 m Trauma US li 93 kritisch 5 J T 32 m Trauma US li 110 überkritisch K R 33 m Trauma US li 62 [1]. Aus diesen Betrachtungen folgt, daß beide Komponenten gemeinsam eher einen konstanten als einen progressiven Einfluß auf die Gesamtkraft haben.…”
Section: Materials Und Methodeunclassified
“…Twelve hours later the distraction force had fallen substantially and reaches a value slightly greater than the final force on the previous days. As the soft tissue has substantial viscoelastic behavior, these are just a transient peak force, and after distraction the force decrease exponentially (Leong et al, 1979) with an average rate of 2.3 N/h the first 3-5 h (Aarnes et al, 2002). The main finding of this study was the differential pattern of forces between the lateral segments observed in unilateral cleft lip and palate subjects.…”
Section: Discussionmentioning
confidence: 63%
“…In the present study, assessment of distraction forces did not allow differentiation between contribution from the soft tissue envelope and the regenerate. Previous investigations have suggested the soft tissue (Aarnes et al, 2002;Gardner et al, 1997), the regenerate (Aronson and Harp, 1994) or both (Gardner et al, 1998) to be the source of the tensile force. The force in the rigid external distractor is a result of the resistance in the composite tissue system, and the interpretation of the results depends on which structure provides the major resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of distraction osteogenesis stress accumulation is modulated by three effects: the mechanical elongation of the gap, the intrinsic viscoelastic nature of soft tissues in the interfragmentary gap (Leong et al 1979;Simpson et al 1996;Nakamura et al 1997;Matsushita et al 1999;Richards et al 1999;Aarnes et al 2002) and the tissue growth/differentiation inside the gap.…”
Section: Introductionmentioning
confidence: 99%